Breaking Barriers and Balancing Bytes: Exploring Work-Life Balance among Female ICT Professionals in a South Telecommunications Company - A PhD Thesis Review - Munyeka, Wiza; Maharaj, Ashika (Journal of Business and Management Review, 2024)
Research Aim: This review examines work-life balance experiences offemale Information and Communications Technology (ICT) professionalsin the South African telecommunications sector from the organization,Telkom, drawing from Wiza Munyeka’s 2021 PhD thesis.Design/methodology/approach: The study, encompassing four researcharticles, employs a mixed-methods approach and is theoreticallygrounded in the Life Course perspective and Border Theory. ResearchResearch Findings:The research unveils Telkom’s proactive measures andemployee awareness regarding work-life balance policies. Telkom utilizeswork life balance policies and programmes namely the Telkom Touch(2018) and Telkom Policy on Hours of Work (Other WorkingOpportunities and Overtime) hours (2015). It emphasizes the universalchallenges faced by female ICT professionals, urging targetedinterventions.Theoretical Contribution/Originality: The study contributes significantlyby introducing the Work-Life Balance Framework, synthesizing keytheories and providing a practical guide for understanding andaddressing challenges in diverse contexts. This research review fills acritical gap in the literature, amplifies the voices of an understudieddemographic, and offers practical implications for organizational policies,interventions, and strategies to foster an inclusive and supportive workenvironment.Keywords: Work life balance; females; Information and CommunicationsTechnology; Life Course Perspective; Border Theory